Serum IL-6 levels of atopic patients with recurrent aphthous stomatitis (RAS) - Nur'aeny, Nanan; Sufiawati, Irna; Suwarsa, Oki; Gurnida, Dida Akhmad (Padjadjaran Journal of Dentistry, 2019)
Introduction: Atopy is a genetic tendency of allergic condition with specific clinical manifestations such as atopic dermatitis (AD), allergic rhinitis (AR), and bronchial asthma (BA). Atopic individuals might experience other health problems that coincide with atopic manifestations, including the appearance of recurrent aphthous stomatitis (RAS) which is an oral mucosal disease that can also be influenced by allergies. This study was aimed to be the preliminary study regarding the level of IL-6 serum in atopic patients who were also having RAS. Methods: Thirty subjects were recruited and grouped into three groups with ten subjects each were group of atopic (dermatitis, allergic rhinitis, or bronchial asthma) with RAS, atopic without RAS, and control. Blood specimens were obtained with an approved institutional board review protocol. This research was cross-sectional research with consecutive sampling method conducted at Dr Hasan Sadikin Hospital Bandung. Results: There were significant differences in IL-6 log levels in all three groups (p < 0.001). The higher IL-6 levels in the group of atopic with RAS might be due to the influence of atopy because this condition can increase the acute inflammation of RAS. IL-6 is a pro-inflammatory marker found in the circulation of atopic and RAS patients. Conclusion: Serum IL-6 levels in the group of atopic patients with RAS is higher than in other groups. Keywords: Serum, IL-6, atopic, recurrent aphthous stomatitis